2019
DOI: 10.1101/589614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shared genetic background between children and adults with attention deficit/hyperactivity disorder

Abstract: AbstractAttention deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder characterized by age-inappropriate symptoms of inattention, impulsivity and hyperactivity that persist into adulthood in the majority of the diagnosed children. Despite several risk factors during childhood predicting the persistence of ADHD symptoms into adulthood, the genetic architecture underlying the trajectory of ADHD over time is still unclear. We set out to study the contribu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…DSM-5 does acknowledge some developmental differences by (i) providing suggestions of how childhood symptoms may present in adolescence or adulthood (such as running or climbing about when it is inappropriate instead presenting as feeling restless ), and (ii) requiring fewer symptoms to meet diagnostic criteria in adulthood ( American Psychiatric Association, 2013 ). Genetic research also suggests that while there is considerable overlapping genetic liability (approximately 66% shared) between child and adult ADHD ( Rovira et al, 2019 ), there is also likely age-specific genetic liability. Both genetic and environmental factors likely contribute to developmental differences in the presentation of ADHD symptoms, for example exposure to stressful life events or different environmental demands.…”
Section: Discussionmentioning
confidence: 99%
“…DSM-5 does acknowledge some developmental differences by (i) providing suggestions of how childhood symptoms may present in adolescence or adulthood (such as running or climbing about when it is inappropriate instead presenting as feeling restless ), and (ii) requiring fewer symptoms to meet diagnostic criteria in adulthood ( American Psychiatric Association, 2013 ). Genetic research also suggests that while there is considerable overlapping genetic liability (approximately 66% shared) between child and adult ADHD ( Rovira et al, 2019 ), there is also likely age-specific genetic liability. Both genetic and environmental factors likely contribute to developmental differences in the presentation of ADHD symptoms, for example exposure to stressful life events or different environmental demands.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the differences we observed between participants with persistent and remittent ADHD might be genomic effects. Moreover, 8.1% of the measured meQTL SNPs-more than one would expect by chance (X = 5.008, p = 0.025)-were associated (unadjusted p-value < 0.05) with adult, persistent ADHD in a recent GWAS meta-analysis (Rovira et al, 2019), but none of the findings survived correction for multiple testing.…”
Section: Differential Methylation Observations In Persistent Adhd Migmentioning
confidence: 95%
“…These findings overall suggest that the genetic contribution to childhood ADHD also contribute to its persistence in adult life. More recently, independent genome-wide association studies of adult ADHD and child ADHD also showed strong genetic correlation between adult ADHD and child ADHD [45]; again suggesting that while ADHD symptoms might show developmental change, the genetic correlates do not appear to be very different.…”
Section: Adhd: What Happens Over Timementioning
confidence: 97%